IMPLEMENTATION OF SUPPLY CHAIN MANAGEMENT AT CV.TINGGAR JAYA FOR WEB-BASED STOCK MONITORING - Ramadan, Mohamad Rizqulloh; Hilabi, Shofa Shofiah; Nurapriani, Fitria; Priatna, Bayu (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
Implementation of Supply Chain Management at CV. Tinggar Jaya is a company warehouse system designed for company needs to coordinate company resources. The problem that occurs at CV. Tinggar Jaya still uses manual methods, from ordering to checking or monitoring stock in the warehouse. Therefore, the solution to this problem is implementing supply chain management at CV. Tinggar Jaya will organize and monitor the warehouse's stock amount using the waterfall system design method with the expected goal of implementing supply chain management to monitor the stock of goods to be more efficient in carrying out this process. Keywords: Warehouse, Supply Chain Management, Goods, Monitoring, Stock, Website